If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(9x-44)=(6x-10)
We move all terms to the left:
(9x-44)-((6x-10))=0
We get rid of parentheses
9x-((6x-10))-44=0
We calculate terms in parentheses: -((6x-10)), so:We get rid of parentheses
(6x-10)
We get rid of parentheses
6x-10
Back to the equation:
-(6x-10)
9x-6x+10-44=0
We add all the numbers together, and all the variables
3x-34=0
We move all terms containing x to the left, all other terms to the right
3x=34
x=34/3
x=11+1/3
| 21-2x3=-51 | | 4(x+3)/5=7 | | f+2f+(2f+2.50)=11.25 | | -6t+8=14 | | -10x+5=-6x—35 | | 10q-2(3q-6)=5(3q-6)-3q-6 | | -c/5=6 | | 6x+2.5=57 | | m+24=-15 | | -1/2=j/4-10/3 | | 11x-7=61 | | 25-0,5d=15 | | 0.135x+0.09(30,000−x)=3,195 | | 6x-32+2x+19=180 | | 3^6y=531441 | | 2.3(x-4)=2x+1 | | 8xP=72 | | 4^(5x)=5^(x+2) | | -7x+9x-10=8-7x | | 2x/2x-15=3/5 | | 9p-2=10-3p | | -2x+5+5+(-x)-5=0 | | 3x+21-91=3x+5=50 | | 8xY=40 | | 12v-14=2v+16 | | 3x+5x+5+3x+30=180 | | 8x+38=-3 | | X2-12x+32=12 | | 4n=9=2(5+2n) | | 10x+12+2x=72 | | x+(-13.3)=-1.5 | | 4n=9=2 |